Enhanced thermoelectric materials based on Cu3SbSe3 for room temperature applications - Hsu, Thiri Zaw (Nanyang Technological University, 2023)
Cu3SbSe3 is a ternary compound that is theorised as a new promising thermoelectric material due to its ultra-low thermal conductivity. Research have been carried out on enhancing thermoelectric performance of Cu3SbSe3 through secondary phase inclusions and different methods of synthesis. However, more investigation is needed for Cu3SbSe3 to be concluded as a high-performance thermoelectric material. Moreover, studies on effects of doping on thermoelectric properties of Cu3SbSe3 have not been widely carried out. Hence, this paper focuses on synthesising pristine Cu3SbSe3 through quenching-annealing and exploring how doping with Ag, Bi, Sn, Pb and Ge dopants on Cu and Sb sites affects thermoelectric performance of Cu3SbSe3. ZEM-3 and Laser Flash Analysis (LFA) were used to carry out thermoelectric measurements. Characterization on morphology was carried out using Scanning Electron Microscopy (SEM) and X-ray Diffraction (XRD). The findings showed that addition of dopants decreased electrical conductivity of Cu3SbSe3 and its thermal conductivity. Although low thermal conductivity is desirable for good thermoelectric materials, the reduced electrical conductivity led to an overall decline in Figure of Merit, zT, and Power Factor, PF, which are indicators of thermoelectric performance. Hence, pristine Cu3SbSe3 had the best thermoelectric properties among all the samples despite having higher thermal conductivity than doped samples. Possible causes for these findings and suggestions for future studies will be addressed in this report.